Short science fiction writer's thinking in the Dewan Kosmik magazine from January to June 2021 - Nik Muhamad Affendi, Nik Rafidah; Jaffar, Siti Rabiatul Adawiah (Human Resource Management Academic Research Society, 2024)
This article discusses the thinking of science fiction short story writers in Dewan Kosmik magazine published by Dewan Bahasa dan Pustaka from January to June 2021. Based on the review of previous studies on science fiction, most science fiction studies only look from an external point of view. The internal aspects, especially the author's thinking, have been less studied by previous researchers. Therefore, research needs to be done to see the internal aspects highlighted by science fiction authors. Accordingly, the researcher used qualitative research methods, bibliography, and text analysis. This study also applied the SPB4K theory founded by Mohd. Yusof Hasan as the basis. The results of the study showed that science fiction short stories display the author's thinking about societal life based on science and technology.